ANALISIS ATAS TEMUAN BERULANG BANTUAN KEUANGAN PARTAI POLITIK DI KABUPATEN TEMANGGUNG - Endah Aprimulki; Abdul Halim (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2021)
This research aims to provide an overview of the accountability process for thefinancial assistance from political party (banparpol) in Temanggung, analyzing thecause of repeated findings in the report of Banparpol in the respective district,also identifying the efforts made by the recipients in respond to the repeated findings.This research employs qualitative approach and case study as the research design,with two political parties, A and B, as the object of the research. The data wascollected by documentation and interview. It involved the chairperson of the party,the treasurer, and parts of the party’s organization as participants.The result shows that the reporting process of financial assistance in both parties,A and B, was conducted by forming a committee for every activity related to thefunding of Banparpol. Each committee reported all of the activities fromimplementation of the event, collecting evidence and documentation of the event,and made event summary. After this report is completed, the treasurer will verifyand compile everything which will then become Banparpol’s report. The factorcausing repeated finding on the respective policial parties’ report were the humanresources’ lack of understanding upon administrative process, the inconsistenciesof political party’s regulation, budget disburstment which is processed in the endof the year, lack of motivation and the inability to obey the regulation. Furthermore,different judgement among the examiner also becomes influencing factor. Anothercaus is cultural dimensions that appear in political party B, which are disobedienceand subborness. Efforts made by political party A to avoid the repeated findingsare choosing a regular place which has already had a well structured administrationand conductiong revisions based on the recommendation of the Audit Board (BPK).The first strategy is also performed by political party B, in addition to recruiting LOto provide assistance in understanding political party’s accountability rules andconsulting to Kesbangpol.This research uses Stewardship theory and compliance theory in identifying factorscontributing to the repeated findings in Banparpol’s acountability report inTemanggung district.